2021
DOI: 10.1111/1750-3841.15775
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of docosahexaenoic acid or conjugated linoleic acid with caffeic acid on ameliorating oxidative stress of HepG2 cells

Abstract: Exploring the synergistic effect of docosahexaenoic acid (DHA) or conjugated linoleic acid (CLA) with caffeic acid (CA) on ameliorating oxidative stress, thereby introducing CA to DHA or CLA will contribute significantly to enhance the bioactivity. We observed that DHA or CLA with CA promoted the recovery of intact individual morphology and the decline of cavities inside the nucleus and apoptosis under the observation of confocal laser scanning microscopy and fluorescent inverted microscope. The activity of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
(74 reference statements)
2
12
0
Order By: Relevance
“…Therefore, we determined the hepatic antioxidative ability and found that 1.5 to 4.5 mg t10,c12-CLA treatment yielded higher GSH-Px and T-AOC activities and decreased the level of MDA in the liver of chicks. These findings are consistent with previous findings ( Qi et al., 2018 ; Liu et al., 2021 ). MDA is a major oxidation product of peroxidized PUFAs and an important indicator of lipid peroxidation.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, we determined the hepatic antioxidative ability and found that 1.5 to 4.5 mg t10,c12-CLA treatment yielded higher GSH-Px and T-AOC activities and decreased the level of MDA in the liver of chicks. These findings are consistent with previous findings ( Qi et al., 2018 ; Liu et al., 2021 ). MDA is a major oxidation product of peroxidized PUFAs and an important indicator of lipid peroxidation.…”
Section: Discussionsupporting
confidence: 94%
“…An interesting observation was made that Pulmozyme ® and DNase I treatment led to the violation of nuclear morphology and disruption of the structural organization of the B16 cells’ chromatin: the nuclei with internal voids were disintegrated and wrinkled and intercellular spaces were expanded ( Figure 4 C). Moreover, nuclear chromatin condensation and fragmentation with the formation of nuclear vacuoles and a large number of polymorphic granules and parietal localization of chromatin close to the nuclear membrane were observed, which characterizes the degradation of nucleosomal DNA, and DNA packing in microparticles, indicating cell death via necrosis or late-stage apoptosis, which is consistent with data in the literature [ 34 , 35 , 36 ]. The detected changes were more pronounced with the i.n.…”
Section: Resultssupporting
confidence: 90%
“…The administration of both Pulmozyme ® and DNase I led to the activation of apoptosis in metastatic foci with an increase in cfDNA concentration. Apoptosis was confirmed by morphological changes in metastases in lungs, where DNase I and especially Pulmozyme ® caused the condensation of chromatin in the form of clumps in the nuclei, and these degenerative changes indicate cell death via necrosis or late-stage apoptosis [ 34 , 35 , 36 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 Studies show that caffeic acid reduces noise-induced oxidative damage in the cochlea, 18 treats atopic dermatitis, 19 and inhibits esophageal 20 and liver cancer. 21 However, most studies focused on the signaling transduction mechanism and did not identify its target at the cell membrane.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Caffeic acid is one of the main active ingredients of coffee; in addition, the content of it in propolis, perilla, hawthorn, lemon, and other common foods is also high . Studies show that caffeic acid reduces noise-induced oxidative damage in the cochlea, treats atopic dermatitis, and inhibits esophageal and liver cancer . However, most studies focused on the signaling transduction mechanism and did not identify its target at the cell membrane.…”
Section: Introductionmentioning
confidence: 99%